Análise da Percepção do Uso de Cigarros Eletrônicos no Brasil por meio de Comentários no YouTube - Dias, Aline; Tanure, Richardy R.; Almeida, Jussara M.; Lima, Helen C. S. C.; Ferreira, Carlos H. G. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the Web, 2024)
The rise of video platforms such as YouTube has revolutionized information sharing and influenced social habits and product consumption. At the same time, the diverse global regulatory landscape and ongoing studies on the health effects of e-cigarettes have led to intense and controversial debates. Amidst this, the production of content about e-cigarettes on the internet is rapidly increasing, particularly on YouTube, one of the most popular video platforms globally and the most popular in Brazil. Despite the growing body of research focused on understanding online interactions with e-cigarettes, there is a lack of comprehensive and detailed temporal analyses that capture the dynamics of the debate and people’s stance towards these products, especially in the Brazilian context. To address this gap, our study aims to investigate the popularity and acceptance of e-cigarettes in Brazil by analyzing YouTube videos and their associated comments. We collected an extensive dataset of videos, channels, comments and their metadata from 2018 to 2023. Our methodology involved analyzing production and engagement metrics, and developing a deep learning-based stance detection model to estimate people’s stance (approval or disapproval) based on comments and quantify the temporal dynamics of these attitudes over the years. Our findings reveal a significant increase in content production and user engagement, indicating a growing public interest, with a notable increase in approving comments on the product. This study fills previous research gaps by offering a comprehensive and pioneering overview of e-cigarette use and public perception in Brazil, emphasizing the need for a more informed discussion among society and regulatory bodies.